2023
DOI: 10.3390/plants12112197
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of PGPR in Salt Stress Tolerance in Crops: Unravelling the Molecular Mechanisms of Cross-Talk between Plant and Bacteria

Gianluigi Giannelli,
Silvia Potestio,
Giovanna Visioli

Abstract: Soil salinity is a major abiotic stress in global agricultural productivity with an estimated 50% of arable land predicted to become salinized by 2050. Since most domesticated crops are glycophytes, they cannot be cultivated on salt soils. The use of beneficial microorganisms inhabiting the rhizosphere (PGPR) is a promising tool to alleviate salt stress in various crops and represents a strategy to increase agricultural productivity in salt soils. Increasing evidence underlines that PGPR affect plant physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 203 publications
1
9
0
Order By: Relevance
“…It has been reported that PGPBs protect plants through increasing the antioxidant ability (Ali et al, 2021 ; Giannelli et al, 2023 ; Gururani et al, 2013 ; Jaleel et al, 2007 ; Kumar et al, 2021 ; Kumawat et al, 2022 ; Singh et al, 2020 ). Plants have evolved two key defense mechanisms against the accumulation of excessive ROS: enzymatic breakdown by SOD, CAT, APX, and other peroxidases (POXs), and antioxidants by small molecules, such as glutathione (GSH), ascorbate acid (AsA), phenolic substances, flavonoids, and carotenoids (Pan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that PGPBs protect plants through increasing the antioxidant ability (Ali et al, 2021 ; Giannelli et al, 2023 ; Gururani et al, 2013 ; Jaleel et al, 2007 ; Kumar et al, 2021 ; Kumawat et al, 2022 ; Singh et al, 2020 ). Plants have evolved two key defense mechanisms against the accumulation of excessive ROS: enzymatic breakdown by SOD, CAT, APX, and other peroxidases (POXs), and antioxidants by small molecules, such as glutathione (GSH), ascorbate acid (AsA), phenolic substances, flavonoids, and carotenoids (Pan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, JPT10 may support osmotic equilibrium in foxtail millet seedlings during salt stress. PGPBs protect plants from salt stress damage through osmotic adjustment (de Andrade et al, 2023 ; Giannelli et al, 2023 ; Kumar et al, 2021 ; Kumawat et al, 2022 ; Ramasamy & Mahawar, 2023 ). The bacterial regulation of the concentration of trehalose, proline, and other osmolytes in plants is one of the mechanisms behind induced plant tolerance to desiccation (Ali & Khan, 2021 ; Sandhya et al, 2010 ; Yang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the inconsistent characteristics of PGPRs, such as the ability of a PGPR to colonize the plant rhizosphere and the ability of bacterial strains to thrive under different environmental conditions, PGPR use in the agriculture industry represents only a small fraction of PGPR use worldwide [ 13 ]. The successful utilization of PGPRs is dependent on several factors, such as their survival in soil and growth-promoting properties [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PGPR are essential in mitigating the adverse effects of salinity and drought stress on plants 24 . By improving beneficial interactions with plant roots, these bacteria enhance the plant's ability to withstand harsh environmental conditions, making them invaluable in promoting crop resilience in saline and arid regions 25 , 26 .
Figure 1 Direct and indirect mechanisms of PGPR in enhancing plant growth and health.
…”
Section: Introductionmentioning
confidence: 99%